Barriers to cataract surgery at primary healthcare level in the eastern zone of peninsular Malaysia: An interpretative phenomenological analysis - Abdul Mutalib, Othman; M.Z., Nurulain; A., Shahir; H., Asma (2017)
The Malaysian Rapid Assessment of Avoidable Blindness Survey in 2014 revealed cataract as the leading cause of blindness and estimated more than six hundred thousand cataract surgery backlog for the whole country. Understanding the barriers to undertake early cataract surgery at primary care level may increase cataract detection and the surgical rate to reduce the prevalence of cataract blindness. Thus the objective of this qualitative study is to explore the barriers to cataract surgery at primary healthcare level from the perspective of patients who are already blind due to cataract. This study involves eleven participants from the state of Kelantan, Terengganu and Pahang. All interviews were carried out in their own home setting. Utilising interpretative phenomenological analysis approach in health psychology, semi-structured interview was tape recorded, transcribed verbatim and analysed using N-Vivo software version 8.0. This study identified two main themes regarding the barriers to cataract surgery at primary care level namely refusal to disclose vision problem and patient-provider related issues. These are the barriers that seem to have prevented them from revealing their visual problems, delay cataract detection and thus the decision for earlier cataract surgery. The subthemes include their belated needs for better sight, delayed awareness and decision to disclose their visual problem to family members or primary healthcare providers. However, appropriate approach and advice from healthcare providers may be able to motivate patients undergo earlier cataract surgery to improve their vision. Thus, further improvement in health education, promotion, vision screening and eyecare delivery system can increase the awareness of the community and also healthcare provider about cataract and improve the strategies towards earlier and more extensive cataract surgery uptake.